PREDICTION OF HIGH POROSITY ZONES IN CLAY ROCKS AT THE EASTERN UKRAINE - Vyzhva, S.; Solovyov, I.; Kruhlyk, V.; Lisny, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new approach for clay rock differentiation using porosity value is proposed. This approach is based on the correlation coefficient values analysis for acoustic impedance and shaliness. The correlation between acoustic impedance and shaliness is absent for shale and rocks with shaliness with small values of porosity.This is due to the absence of physical links between them. For rocks with clay porosity, the correlation between acoustic impedance and shale content is relevant. In this case, both correlation coefficient and shale content in rocks increase. For rocks with high shaliness the correlation coefficient between acoustic impedance can be higher than correlation coefficient between acoustic impedance and porosity. Thereb, in this case the shale fraction of rocks is a carrier of porosity. This fraction controls distribution of acoustic impedance values at the physical level. The new technology of detecting clay rocks with high porosity using seismic and wells data is developed. This technology allows constructing porosity values distributions in the clay rocks. The prognosis of the clay rocks zones with increased porosity is completed. For solution of this task the seismic data is used. The geophysical data obtained from three wells at this area is used as well. Constructed model of rocks physical property coincides with drilling and testing data in these three wells. Geological section of this area is characterized by high amount of clay rocks and small amount of sandy layers. These sandy layers have no industrial flow rate of hydrocarbons. Based on the results obtained, the authors came to particular conclusions concerning natural gas production in this area.